2010
DOI: 10.1007/s00276-010-0644-2
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular innervations of muscle flaps that are commonly used in clinical settings

Abstract: The six muscles are divided into several compartments by the tendon or nerve branches, and all of them make good donor tissue for muscle compartment transfer in reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Similar to two Chinese cadaveric studies by Boo-Chai, [1984] [24] and Yu et al, [2010] [25] , the majority of the specimens demonstrated a single branch coursing deep to the Sartorius muscle proximally with some specimens having 2 to 3 subbranches to the muscle. However, 21.43%, of our specimens had 2-3 twigs arising directly from the anterior branch and coursing deep to the muscle.…”
Section: Branching Patternssupporting
confidence: 80%
“…Similar to two Chinese cadaveric studies by Boo-Chai, [1984] [24] and Yu et al, [2010] [25] , the majority of the specimens demonstrated a single branch coursing deep to the Sartorius muscle proximally with some specimens having 2 to 3 subbranches to the muscle. However, 21.43%, of our specimens had 2-3 twigs arising directly from the anterior branch and coursing deep to the muscle.…”
Section: Branching Patternssupporting
confidence: 80%
“…Each compartment has its own muscle fiber direction and unique sites of origins and endings that distinguishes it from the other compartment. Each compartment has an independent function that can be separated as a flap in surgery [18]. The main nerve was divided into many minor branches after entering the superficial and deep heads; these minor branches were densely distributed at the middle area of the two heads, if we transfer each one of the heads in reconstructive operation, it could obtain good muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle acts as the shoulder extensor, adductor and internal rotator. The nerve supply is via the thoracodorsal nerve running deep to the muscle [48,49].…”
Section: Discussionmentioning
confidence: 99%